Iodine nutritional status and its associations with thyroid function of pregnant women and neonatal TSH - Fan, Lijun; Bu, Ye; Chen, Shiqi; Wang, Sihan; Zhang, Wei; He, Yan; Sun, Dianjun (Frontiers in Endocrinology, 2024)
Iodine serves as a crucial precursor for the synthesis of thyroid hormones and plays an import role in both pregnant women and their offspring. The relationships between iodine nutritional status and maternal thyroid function and neonatal outcomes remain inconclusive in areas with adequate iodine nutrition. This study aims to investigate their correlations. Blood, morning urine and 24-hour urine were collected from the pregnant women to measure thyroid functions, serum iodine concentration (SIC), morning urine iodine concentration (UIC) and 24-hour urine iodine excretion (24-hour UIE). Indicators of their offspring’s neonatal indexes were recorded. A total of 559 pregnant women were enrolled in this study. The iodine indicators including Tg, 24-hour UIE and morning UIC were significantly different among the euthyroid pregnant women and those with different thyroid disorders. The levels of FT3, FT4, and SIC exhibited a gradual decline and the concentration of TSH exhibited a gradual increase trend throughout the progression of pregnancy in euthyroid pregnant women. There were no significant differences in neonatal outcomes and neonatal TSH values among euthyroid pregnant women and thyroid disorders pregnant women. SIC had a significant impact on maternal FT4 levels throughout all three trimesters, with varying degrees of importance observed in each trimester. TSH level emerged as the primary determinant of FT4 during the first trimester, while SIC exerted a predominant influence on FT4 levels in the second and third trimesters. The prevalence of thyroid disorders in pregnant women was the lowest when the SIC of pregnant women was probable in the range of 60~70 μg/L, 24-hours UIE was in the range of 250~450 μg, and Tg was in the range of 9~21 μg/L. Maternal TSH exhibited a notable influence on neonatal TSH levels, particularly at the 50th and 75th quantiles. Among the iodine nutritional indicators, SIC and morning UIC demonstrated higher AUC values for abnormal FT4 and TSH, respectively. In conclusion, the iodine nutrition status of pregnant women exerts an impact on their thyroid function and prevalence of thyroid disorders, and neonatal TSH was affected by maternal TSH. SIC may be a better indicator for iodine nutritional assessment than other indexes.